Stability under Seepage Flow Conditions of a Tunnel Face Reinforced by Bolts. (2017) - Perazzelli, P.; Cimbali, G.; Anagnostou, G.
Abstract: We propose a computational method for assessing bolt reinforcement of the tunnel face in cohesive frictional soils and weak rocks under seepage flow conditions. The method is based on limit equilibrium factors and can be applied to reinforcement layouts that are arbitrary in terms of the spacing, length, longitudinal overlapping and installation sequence of the bolts. An investigation is made into the influence of water table height on the stability of a reinforced face. In particular, we show that, if the gradient of the hydraulic head is high, then tensile failure of the ground ahead of the face may be more critical than shear failure. For an approximate hydraulic head distribution in the ground around the tunnel face and assuming uniform face reinforcement, we derive a closed-form solution for the necessary bolting density.